Neuropsychological deficits in HIV seropositive patients in different stages of the disease process - Μεσσήνης, Λάμπρος; Τσάκωνα, Ιωάννα; Κόλλαρας, Παναγιώτης; Μαλεφάκη, Σόνια; Παπαθανασόπουλος, Παναγιώτης (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF